ANALYSIS OF THE EFFECTS OF LIQUIDITY, ACTIVITIES, LEVERAGE, AND PROFITABILITY ON FIRM VALUE IN RETAIL TRADE SUBSECTOR (IDX) 2015-2020 PERIOD - Yulianti, Riska; Dewi Syarif, Andam (Dinasti International Journal of Digital Business Management, 2021)
This research intends to determine the effect of liquidity, activity, leverage, and profitability on company value. The population of this research is the entire IDX retail trade subsector in 2015-2020 as many as 25 companies and the number of samples is 14 companies. The data analysis method used in the research is Panel Data Regression and the best model is the Random Effect Model. The results of the research partially found that liquidity (CR), activity (TATO), and leverage (DER) did not affect PBV, while profitability (NPM) had a positive effect on PBV. The research results simultaneously found that liquidity (CR), activity (TATO), leverage (DER), and profitability (NPM) had an impact on PBV.